ANALISIS RUANG TERBUKA HIJAU (RTH) KOTA MANADO - Ravena R. R. Pangemanan; O. Esry. H. Laoh; Theodora M. Katiandagho (Sam Ratulangi University, 2017)
This study aims to identify the Green Open Space of Manado City and to study the Green Open Space in Manado City by comparing with the determination of green open space based on Law No. 26 of 2007 article 29 on spatial planning. The study was conducted from February to Jully 2017, using secondary data. Secondary data were obtained from the Central Bureau of Statistics (BPS) of Manado City, and the Office of the Regional Development Planning Board (BAPPEDA) of Manado City. Data analysis used is availability analysis, requirement analysis (by area), and adequacy analysis. The results showed that the availability of public green space in Manado City has not reached the target or 20% for public open space and in Manado City there are only 2283,25 hectares or around 14,51%, while for private Green Open Space in Manado city is very wide as 10223, 57 hectares or around 63,01%, has exceeded up to six times the private Green Open Space target of 10%. For that presumably the government can regulate the spatial related to Green Open Space in an effort to improve environmental quality in Manado City, especially in public green space that is still less than the target.